Crossings to adulthood: how diverse young Americans understand and navigate their lives - Swartz, Teresa Toguchi; Hartmann, Douglas; Rumbaut, Rubén G. (Youth in a globalizing world, 2017)
Crossings to Adulthood: How Diverse Young Americans Understand and Navigate their Lives' assembles chapters written by members and affiliates of the Research Network on Transitions to Adulthood on pressing issues facing young, coming-of-age Americans in an increasingly diverse, globalizing world. Based on over 400 interviews with young adults from different racial, class and regional backgrounds, the chapters provide an in-depth look at how young Americans understand their lives and the challenges, risks, and opportunities they experience as they move into adulthood during changing and uncertain times. Chapters focus on how these young adults understand markers of adulthood such as leaving home, launching careers, and forming relationships, as well as issues particularly salient to them including politics, diversity, identity, and acculturation